1980
DOI: 10.1111/j.1365-2389.1980.tb02077.x
|View full text |Cite
|
Sign up to set email alerts
|

The Water Balance of an Agricultural Catchment. I. Estimation of Evaporation From Soil Water Records

Abstract: Errors of measurement of soil water content with the neutron probe can be made small enough for most water balance studies; and apart from the possible damage resulting from access tube implacement, they can be readily specified. A more important problem is estimating how much water is lost from soil by drainage.A simple, graphical method is described to distinguish between drainage and evaporation from soil, based upon identification of the maximum depth at which measurable quantities of water are extracted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Furthermore, D can be found by employing a time-integrated form of Darcy's law (Klaij and Vachaud, 1992). Alternatively, the distinction between E and D can be made by determination of the zero-flux-plane, ZFP (McGowan and Williams, 1980), above which E occurs and below which drainage takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, D can be found by employing a time-integrated form of Darcy's law (Klaij and Vachaud, 1992). Alternatively, the distinction between E and D can be made by determination of the zero-flux-plane, ZFP (McGowan and Williams, 1980), above which E occurs and below which drainage takes place.…”
Section: Introductionmentioning
confidence: 99%
“…The water balance (WB) method has been widely used in citrus (Koo and Sites, 1955;Koo, 1961;Kalma and Stanhill, 1969;Hoffman et al, 1982;Smajstrla et al, 1982;Wiegand and Swanson, 1982;Sharples et al, 1985;Castel et al, 1987;Metochis, 1989;Castel andBuj, 1990, 1993;Morgan, 1992;Durán, 1993;Sepaskhah and Kashefipour, 1995;Fares and Alva, 1999;Grismer, 2000) and in other crops (McGowan and Williams, 1980;Vachaud et al, 1985;Moreno et al, 1988;Andreu et al, 1997).…”
Section: Resumen Balance Hídrico Y Estimación Del Coeficiente De Cultmentioning
confidence: 99%
“…With regard to the last parameter the results of McGowan and Williams (1980) with rain fed wheat (Triticum aestivum L.) should be considered. These authors found large variation in changes of stored soil water, measured in profile replicates.…”
Section: Resumen Balance Hídrico Y Estimación Del Coeficiente De Cultmentioning
confidence: 99%
“…This can hamper the NWM from sensing small changes in soil water content brought about by evaporation from the soil surface. Secondly, the NWM reading errors mostly occur in the top horizon of the soil profile where there is a possibility of radiation escaping through the surface and hence not giving a fully representative reading of the water content (McGowan and Williams, 1980). This failure of the NWM to observe daily change in water content, caused (Evett et al, 2002;Heng et al, 2002;Mwale et al, 2005;Mounzer et al, 2008;Vera et al, 2009).…”
Section: Comparison Of Dfm Probes and Nwm For Measuring Evaporationmentioning
confidence: 99%
“…The NWM has been used to measure soil water content at different points in time and, if all the other components of the soil water balance equation are measured, it is possible to calculate the loss of soil water through evaporation from the soil surface (McGowan and Williams, 1980;Bennie et al, 1994;1998). With the application of the same principle of monitoring change, some studies quantifying evaporation using capacitance probes have also been done (Verhoef et al, 2006;Mounzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%